The Effect of System Quality, Information Quality and Service Quality on User Satisfaction of E-Learning System - Achmadi, Achmadi; Siregar, Amelia Oktrivina (The International Journal of Business Review (The Jobs Review), 2021)
The study aims at analyzing and explain the influence of system quality, information quality, service quality to user satisfaction e-learning system in the Master of Accounting. Total population of this study were 451 students with a total sample of 82. The sampling technique using proportional random sampling. The analytical method used GSCA (Generalized Structured Component Analysis). The results showed that the system quality, information quality, and service quality significantly influence user satisfaction e-learning system. The better the perception of the quality system, the quality of information, and the quality of service it will further increase user satisfaction.Â